2018
DOI: 10.3847/1538-4357/aa9e53
|View full text |Cite
|
Sign up to set email alerts
|

Circumnuclear Multi-phase Gas in the Circinus Galaxy. I. Non-LTE Calculations of CO Lines

Abstract: In this study, we investigate the line emissions from cold molecular gas based on our previous "radiation-driven fountain model" (Wada et al. 2016), which reliably explains the spectral energy distribution of the nearest type 2 Seyfert galaxy, the Circinus galaxy. Using a snapshot of the best-fit radiation-hydrodynamic model for the central r ≤ 16 pc, in which non-equilibrium X-ray-dominated region chemistry is solved, we conduct post-processed, non-local thermodynamic equilibrium radiation transfer simulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 52 publications
11
29
0
1
Order By: Relevance
“…Wada et al (2016) applied this radiation-driven fountain model to the Circinus galaxy, which is one of the closest (4.2 Mpc: Freeman et al 1977) type-2 AGN. The model is consistent with several observed features, such as the infrared spectral energy distribution (SED, Wada et al 2016), the dynamics of atomic/molecular gas (Wada et al 2018a;Izumi et al 2018;Uzuo et al 2021), distribution of ionized gas in the NLR (Wada et al 2018b), and broadband X-ray spectra (Buchner et al 2021). Mizumoto et al (2019) also suggested that this kind of dust driven wind may play an important role to the warm absorber acceleration.…”
Section: Introductionsupporting
confidence: 83%
“…Wada et al (2016) applied this radiation-driven fountain model to the Circinus galaxy, which is one of the closest (4.2 Mpc: Freeman et al 1977) type-2 AGN. The model is consistent with several observed features, such as the infrared spectral energy distribution (SED, Wada et al 2016), the dynamics of atomic/molecular gas (Wada et al 2018a;Izumi et al 2018;Uzuo et al 2021), distribution of ionized gas in the NLR (Wada et al 2018b), and broadband X-ray spectra (Buchner et al 2021). Mizumoto et al (2019) also suggested that this kind of dust driven wind may play an important role to the warm absorber acceleration.…”
Section: Introductionsupporting
confidence: 83%
“…The dust particles in the central r < r sub ∼ 0.1-a few parsecs are sublimated owing to the heating by the central radiation. The radiation forms conical ionized gas (Narrow emission-line region) and also contributes to producing outflows of the dusty gas and torus (Wada 2012;Wada et al 2018;Izumi et al 2018). In the mid-plane of the torus, cold, dense gas forms a thin disk, where icy dust particles can present beyond the snow-line r snow .…”
Section: Introductionmentioning
confidence: 99%
“…(2016) geometry from their final simulation time step. Figure 1 shows the geometry for a black hole mass of M BH = 2 × 10 6 M and 20% Eddington rate, suitable for comparison to Circinus (see Wada et al 2016Wada et al , 2018aIzumi et al 2018;Wada et al 2018b, for comparison with infrared SEDs, atomic/molecular gas, and ionized gas observations, respectively). The model has a Compton-thick LOS column density only under edgeon viewing angles (consistent with the infrared analysis of Circinus by Wada et al 2016).…”
Section: Wada's Radiative Fountain Modelmentioning
confidence: 99%

Physically motivated X-ray obscurer models

Buchner,
Brightman,
Baloković
et al. 2021
Preprint
Self Cite